2017
DOI: 10.1002/2017sw001687
|View full text |Cite
|
Sign up to set email alerts
|

The Secular Variation of the Center of Geomagnetic South Atlantic Anomaly and Its Effect on the Distribution of Inner Radiation Belt Particles

Abstract: In this study, we carry out a comprehensive analysis of secular variation of the South Atlantic Anomaly. The center location of the South Atlantic Anomaly (SAA) is derived from the proton flux measurements of different energy channels by SAMPEX (Solar Anomalous and Magnetospheric Particle Explorer)/PET (Proton/Electron Telescope). The results are compared with National Oceanic and Atmospheric Administration/Medium Energy Proton and Electron Detector observations and the International Geomagnetic Reference Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The trapped radiation environment, consisting of large amounts of energetic charged particles, can be potentially harmful to human beings and space vehicles immerged in it (Qin et al, 2014). This high radiation zone at a low altitude has potential threat to low orbit spacecrafts, such as weather-forecast satellites and manned missions (Ye et al, 2017).Although most of the effects of SAA have been studied for its external interactions with the upper atmosphere and magnetosphere, the https://doi.org/10.5194/npg-2020-15 Preprint. Discussion started: 18 May 2020 c Author(s) 2020.…”
Section: The South Atlantic Anomalymentioning
confidence: 99%
“…The trapped radiation environment, consisting of large amounts of energetic charged particles, can be potentially harmful to human beings and space vehicles immerged in it (Qin et al, 2014). This high radiation zone at a low altitude has potential threat to low orbit spacecrafts, such as weather-forecast satellites and manned missions (Ye et al, 2017).Although most of the effects of SAA have been studied for its external interactions with the upper atmosphere and magnetosphere, the https://doi.org/10.5194/npg-2020-15 Preprint. Discussion started: 18 May 2020 c Author(s) 2020.…”
Section: The South Atlantic Anomalymentioning
confidence: 99%
“…This creates a region with reduced magnetic field intensity, namely the South Atlantic Anomaly (SAA), which is located approximately on the eastern coast of Brazil. The SAA is a place where the radiation of the inner van Allen belt approaches the closest to Earth [2,3]. One of the manifestations of the SAA is the enhanced count rate of protons and electrons coming from the inner radiation belt [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the SAA moves steadily in a northwest direction. This movement has been registered by measurement of the magnetic field [8,9] and by radiation [2,3,[10][11][12][13][14][15][16][17][18][19][20][21]. Table 1 summarizes the publications that have focused on examining the drift of the radiation center of the SAA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAA of proton radiation belt drifts westward at a rate about 0.1–1.0°/year, following the drift of the geomagnetic‐field configuration, and drifts northward at a rate about 0.06–0.16°/year. The westward and northward drifting rates are related to the altitude of SAA (e.g., Badhwar, 1997; Bühler et al, 2002; Casadio & Arino, 2011; Fürst et al, 2009; Grigoryan et al, 2008; Heynderickx, 1996; Jones et al, 2017; Konradi et al, 1994; Qin et al, 2014; Schaefer et al, 2016; Ye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%